Anaesthetic depth and delirium after major surgery: a randomised clinical trial. (November 2021) - Evered, Lisbeth A.; Chan, Matthew T.V.; Han, Ruquan; Chu, Mandy H.M.; Cheng, Benny P.; Scott, David A.; Pryor, Kane O.; Sessler, Daniel I.; Veselis, Robert; Frampton, Christopher; Sumner, Matthew; Ayeni, Ade; et al.
Abstract: Background: Postoperative delirium is a serious complication of surgery associated with prolonged hospitalisation, long-term cognitive decline, and mortality. This study aimed to determine whether targeting bispectral index (BIS) readings of 50 (light anaesthesia) was associated with a lower incidence of POD than targeting BIS readings of 35 (deep anaesthesia). Methods: This multicentre randomised clinical trial of 655 at-risk patients undergoing major surgery from eight centres in three countries assessed delirium for 5 days postoperatively using the 3 min confusion assessment method (3D-CAM) or CAM-ICU, and cognitive screening using the Mini-Mental State Examination at baseline and discharge and the Abbreviated Mental Test score (AMTS) at 30 days and 1 yr. Patients were assigned to light or deep anaesthesia. The primary outcome was the presence of postoperative delirium on any of the first 5 postoperative days. Secondary outcomes included mortality at 1 yr, cognitive decline at discharge, cognitive impairment at 30 days and 1 yr, unplanned ICU admission, length of stay, and time in electroencephalographic burst suppression. Results: The incidence of postoperative delirium in the BIS 50 group was 19% and in the BIS 35 group was 28% (odds ratio 0.58 [95% confidence interval: 0.38–0.88]; P =0.010). At 1 yr, those in the BIS 50 group demonstrated significantly better cognitive function than those in the BIS 35 group (9% with AMTS ≤6 vs 20%; P <0.001). Conclusions: Among patients undergoing major surgery, targeting light anaesthesia reduced the risk of postoperative delirium and cognitive impairment at 1 yr. Clinical trial registration: ACTRN12612000632897 .